156 MECHANISMS AFFECTING T-CELL PRIMING AND DIFFERENTIATION IN THE ELDERLY. (1st January 2006) - Lee, W. -W.; Cui, D.; Weyand, C. M.; Goronzy, J. J.
Abstract : Purpose: The ability to mount primary immune responses is severely compromised with age. Although thymic production of new T cells dwindles early during adulthood, size and repertoire contraction of nave T cells explain defective immunocompetence only after the age of 75 years. We have hypothesized that cellular defects in aged nave T cells impair their ability to respond and to clonally expand to activation stimuli. Methods: Purified nave CD45RA + CD4 + T cells from young (20 to 31 years, n = 10) and old (65 to 81 years, n = 10) were co-cultured with myeloid dendritic cells and the superantigen TSST-1 to mimic in vitro priming. The system allows for separately examining high-affinity (Vb2 + T cells) and low-affinity (Vb2 2 T cells) T-cell responses. Dendritic cells were derived from a young donor. Cell cycle entry and progression were monitored by CSFE staining. Cell activation and differentiation were assessed by gene array and flow cytometry. Results: T-cell activation was intact in aged nave T cells, even after low-affinity interaction. In the young, 87.7 6 8.8% of high-affinity and 10.5 6 3.8% of low-affinity T cells entered the cell cycle compared to 87.3 6 11.8 and 9.7 6 4.3 in the old. T cells after high-affinity activation showed a more rapid cell cycle progression; however, again, there was no age-dependent difference. Flow cytometric studies of chemokine receptors documented differentiation of primed T cells, irrespective of the age of the donor. Gene array studies allowed the identification of several differentiation pathways that were intact in the elderly. However, there was a selective defect in the regulation of several thiol systems, which was confirmed by real-time PCR in a second independent cohort of young and old individuals. Conclusions: In sharp contrast to murine studies, human nave T cells in the elderly are able to respond to high- and low-affinity T-cell receptor ligands, enter the cell cycle, and proliferate without significant delay in cell cycle progression, suggesting effective compensation for telomere loss. The abnormal induction of selected antioxidant thiols is a promising target to understand age-dependent immune defects.